High performance dengue virus antigen-based serotyping-NS1-ELISA (plus): A simple alternative approach to identify dengue virus serotypes in acute dengue specimens. - Tanapan Prommool; Pongpawan Sethanant; Narodom Phaenthaisong; Nattaya Tangthawornchaikul; Adisak Songjaeng; Panisadee Avirutnan; Dumrong Mairiang; Prasit Luangaram; Chatchawan Srisawat; Watchara Kasinrerk; Sirijitt Vasanawathana; Kanokwan Sriruksa; et al. (Public Library of Science (PLoS), 2021)
Dengue hemorrhagic fever (DHF) is caused by infection with dengue virus (DENV). Four different serotypes (DENV1-4) co-circulate in dengue endemic areas. The viral RNA genome-based reverse-transcription PCR (RT-PCR) is the most widely used method to identify DENV serotypes in patient specimens. However, the non-structural protein 1 (NS1) antigen as a biomarker for DENV serotyping is an emerging alternative method. We modified the serotyping-NS1-enzyme linked immunosorbent assay (stNS1-ELISA) from the originally established assay which had limited sensitivity overall and poor specificity for the DENV2 serotype. Here, four biotinylated serotype-specific antibodies were applied, including an entirely new design for detection of DENV2. Prediction of the infecting serotype of retrospective acute-phase plasma from dengue patients revealed 100% concordance with the standard RT-PCR method for all four serotypes and 78% overall sensitivity (156/200). The sensitivity of DENV1 NS1 detection was greatly improved (from 62% to 90%) by the addition of a DENV1/DENV3 sub-complex antibody pair. Inclusive of five antibody pairs, the stNS1-ELISA (plus) method showed an overall increased sensitivity to 85.5% (171/200). With the same clinical specimens, a commercial NS1 rapid diagnostic test (NS1-RDT) showed 72% sensitivity (147/200), significantly lower than the stNS1-ELISA (plus) performance. In conclusion, the stNS1-ELISA (plus) is an improved method for prediction of DENV serotype and for overall sensitivity. It could be an alternative assay not only for early dengue diagnosis, but also for serotype identification especially in remote resource-limited dengue endemic areas.